سطوة عناصير اللغوية فى شرح الحديث - Sa’diyah, Fatichatus (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2019)
The point of this article is to explain that language element either vocabulary of arabic language, nahwuism or balaghaism and phonetics had dominated the explanation of hadis either the explanation by using tahlili> methode, ijma>li> methode or muqa>rin methode since the first periode of hadis explanation. Language orientation, rare term of hadis text, reader necessary, the background knowladge of explainer became the evidence that language element was dominate hadis explanation.